ANALISIS DIFFERENTIAL COST DAN OPPORTUNITY COST DALAM PENGAMBILAN KEPUTUSAN MEMBELI ATAU MEMPRODUKSI SENDIRI PADA INDUSTRI RUMAH PANGGUNG WOLOAN - Mongdong, Romeo Fersi; Morasa, Jenny; Wokas, Heince (Universitas Sam Ratulangi, 2015)
The business world today is characterized by increasing competition among existing companies. Competition occurs in all sectors of the economy both industry, trade, and services. One of the decisions that must be taken in planning at every alternative is to buy or produce itself a component of raw materials. Differential cost are related to the opportunity cost, which is the differential cost incurred costs as a result of certain decisions while the opportunity cost is the cost incurred when choosing a decision. The purpose of this study to analyze the differential costs and opportunity costs in the decision to buy or produce their own on Industri Rumah Panggung Woloan. The analytical method used is descreptive quantitative. Result of the differential cost analysis showed that the right decisions can be taken by the management company the manufactures its own because getting a hihgter differential gain, compared to buying from outside. While the opportunity cost of the buying raw materials from outside is more profitable, thus producing itself becomes more expensive. Should the leadership Industri Rumah Panggung Woloan produce their own wood from the outside becauseit would be more adventageous, compared to taking wood there are kept alone.